Identifying Patients with COPD in Need for Psychosocial Care Through Screening with the HSCL-25 and the CCQ Mental State. (2nd January 2018) - Maters, Gemma A.; Pool, Grieteke; Sanderman, Robbert; Wempe, Johan B.; Fleer, Joke
ABSTRACT: High levels of psychological distress are documented in patients with COPD. This study investigates the extent to which patients with a high score on the Hopkins Symptoms Checklist-25 (HSCL-25) or with a high score on the Mental State scale of the Clinical COPD Questionnaire (CCQ) endorse a need for psychosocial care, and investigates several characteristics of patients with a need. Outpatients with COPD of the Department of Pulmonary Diseases of a University Medical Center were assessed with the HSCL-25, CCQ and a question on need for psychosocial care. For patients indicating a need, the percentage of patients with HSCL-25 ≥39 was compared with the percentage of patients with CCQ Mental State >2 and tested with a Chi-square. In total 323 patients participated; 57% of them were distressed according to the HSCL-25 (≥39) and 20% according to the CCQ Mental State (>2); 28% reported a need for psychosocial care. For patients reporting a need for psychosocial care a higher percentage was identified by the HSCL-25 than by the CCQ Mental State (χ 2 = 9.41, p <. 002) and they were younger than patients without a need ( t = 4.48, p <. 001). No differences existed for sex, FEV1, FEV1 % predicted or medical comorbidities. The HSCL-25 identified more patients in need than the CCQ Mental State scale. However, not all patients with a need were identified. No relationship was found between need for psychosocial care and illness variables or comorbidities. Distress screening is questioned as the most effective way to identity patients with COPD in need for psychosocial care.